Long-term seizure dynamics are determined by the nature of seizures and the mutual interactions between them - Kudlacek, Jan; Chvojka, Jan; Kumpost, Vojtech; Hermanovska, Barbora; Posusta, Antonin; Jefferys, John G. R; Maturana, Matias I; Novak, Ondrej; Cook, Mark J; Otahal, Jakub; Hlinka, Jaroslav; Jiruska, Premysl (Neurobiology of disease, 2021)
The seemingly random and unpredictable nature of seizures is a major debilitating factor for people with epilepsy. An increasing body of evidence demonstrates that the epileptic brain exhibits long-term fluctuations in seizure susceptibility, and seizure emergence seems to be a consequence of processes operating over multiple temporal scales. A deeper insight into the mechanisms responsible for long-term seizure fluctuations may provide important information for understanding the complex nature of seizure genesis. In this study, we explored the long-term dynamics of seizures in the tetanus toxin model of temporal lobe epilepsy. The results demonstrate the existence of long-term fluctuations in seizure probability, where seizures form clusters in time and are then followed by seizure-free periods. Within each cluster, seizure distribution is non-Poissonian, as demonstrated by the progressively increasing inter-seizure interval (ISI), which marks the approaching cluster termination. The lengthening of ISIs is paralleled by: increasing behavioral seizure severity, the occurrence of convulsive seizures, recruitment of extra-hippocampal structures and the spread of electrographic epileptiform activity outside of the limbic system. The results suggest that repeated non-convulsive seizures obey the 'seizures-beget-seizures' principle, leading to the occurrence of convulsive seizures, which decrease the probability of a subsequent seizure and, thus, increase the following ISI. The cumulative effect of repeated convulsive seizures leads to cluster termination, followed by a long inter-cluster period. We propose that seizures themselves are an endogenous factor that contributes to long-term fluctuations in seizure susceptibility and their mutual interaction determines the future evolution of disease activity.
Keywords: tetanový toxin; potkani Sprague-Dawley; Rats, Sprague-Dawley; Epilepsy, Temporal Lobe; zvířata; Rats; epilepsie temporálního laloku; elektroencefalografie; Time Factors; mužské pohlaví; záchvaty; Electroencephalography; Rats, Wistar; Seizures; časové faktory; krysa rodu Rattus; potkani Wistar; Animals; Tetanus Toxin; Male